Can young dancers skip/recover from patellofemoral pain? A two-year follow-up. Issue 3 (2nd July 2020) - Steinberg, Nili; Tenenbaum, Shay; Itzhak, Siev-Ner; Aviva, Zeev
ABSTRACT: Aiming to follow the prevalence of patellofemoral pain (PFP) among young dancers over 2-years, and to assess the prevalence of re-injured/recovered dancers; 67 dancers (aged 12.8 ± 0.5) were screened for PFP at baseline, 65 dancers at 1 st follow-up and 51 dancers at 2 nd follow-up. All dancers (46) that took part in all the 3 screenings had at least one episode of PFP along the screenings. No dancers recovered in the 1 st follow-up, yet 40.5% of the dancers with PFP at the 1 st follow-up recovered in the 2 nd follow-up. Along the 3 screenings, 23.9%, 34.8%, and 41.3% of the dancers had 1, 2 or 3 PFP episodes, respectively. None of the dancers skipped PFP along the 3 screenings. A high prevalence of dancers had sustained PFP along the 2 follow-ups, with low recovery rate. Dancers and teachers should be alert to the need for devising modifications of training and injury prevention strategies from young age.